Prevalence of Hymenolepis nana in wild rats in Surabaya City, East Java - Dwi Putri Rahmawati; Suwanti, Lucia Tri; Mufasirin; Endang Suprihati; Poedji Hastutiek; Kusnoto; Heni Puspitasari; Alasrorik, Muhammad Hizbulloh (Journal of Parasite Science, 2025)
Hymenolepiasis is one of the neglected zoonotic diseases in humans, caused by the cestodes Hymenolepis nana and Hymenolepis diminuta. Its definitive hosts are rodents (mostly rats). This study aims to identify the morphology both microscopically and macroscopically. This research is a laboratory exploratory research and the sampling method uses purposive sampling technique. The samples used in this study amounted to 100 samples of wild rats that had been trapped and then necropsied, worms obtained from the digestive tract were stained with dark red stain and observed with a microscope. The results showed that microscopic morphological examination showed that the anterior part of the H. nana worm had hooks and crowns. The overall prevalence of H. nana worms was found to be 18% (18/100). The prevalence of H. nana in wild rats in Surabaya City in Rattus tanezumi was 16% (12/77). Rattus novergicus in Surabaya area with positive samples was 26% (6/23). Morphology in H. nana worms has a distinctive difference. The anterior part of H. nana has hooks that surround the rostellum, the anterior part has a ‘crown of hooks’.